Cho các tập hợp \(A=\{a;b;c\}\), \(B=\{b;c;d\}\), \(C=\{b;c;e\}\). Khẳng định nào sau đây đúng?
![]() | \(A\cup\left(B\cap C\right)=\left(A\cup B\right)\cap C\) |
![]() | \(A\cup\left(B\cap C\right)=\left(A\cup B\right)\cap\left(A\cup C\right)\) |
![]() | \(\left(A\cup B\right)\cap C=\left(A\cup B\right)\cap\left(A\cup C\right)\) |
![]() | \(\left(A\cap B\right)\cup C=\left(A\cup B\right)\cap C\) |
Chọn phương án B.
Từ (1) và (2) suy ra \(A\cup\left(B\cap C\right)=\left(A\cup B\right)\cap\left(A\cup C\right)\).